Tingkat Adopsi dan Difusi Terhadap Teknologi Budidaya Ikan Kelemak (Leptobarbus hoevanii) Dalam Keramba Di Desa Ranah Kecamatan Kampar Kabupaten Kampar Provinsi Riau - Efintia Putri; Kusai '; Firman Nugroho (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
This research was conduted on 5 to 12 June 2013 in Ranah Village, sub-regent of Kampar that located in regent of Kampar Riau. This research was determined purposively with survey methode. Number of cultivators of Kelemak Fish were 30 of 125 populations taken as the respondent with random sampling. The Adoption Rank for Kalemak Cultvators was in medium category, and Technology adoption Package has been match was medium too because the cultivators havent been used all technology package from stakeholder because that technology so hard to implemented. The suggested Package of the research was location and lay out selection, design, clean of device and tool. The purpose of this study was to collect and analyze information on: characteristics of fish farmers in cages fish floating cultivation both internal and external, to measure adoption level of fish farming in floating cages, analyze the relationship between the farmer characteristic with rate adoption by use coefficient test Spearman rank correlation, and describe the diffusion accelaration procest occured in village of domains. For the diffusion accelaration of the cultivator in Ranah Village have classified low adoption that consist of poor population, low education, no update information more and relation with the stakeholder. Keyword : Adoption , Aquaculture in cages, Leptobarbus hoevanii